Pendampingan Manajemen Kelompok Sadar Wisata (Pokdarwis) Untuk Peningkatan Kapasitas Organisasi Desa Wisata Ngargogondo - Islami, Fitrah Sari; Novitaningtyas, Ivo; Agustin, Hesti (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This community service activity aims to improve the understanding and skills of tourism village managers (pokdarwis) regarding institutional management, tour package management, and tourism service management. The method of community service activities is carried out using lectures, tutorials, and discussions. The results of the implementation of this program show that the understanding and skills of partners regarding institutional management, tour package management, and tourism service management have increased. Thus, it is hoped that the existence of the Ngargogondo Tourism Village can continue to develop and continue to provide a positive impact on the surrounding community. In addition, with optimal management, it is hoped that this tourism village can support Borobudur Temple as a strategic national tourism area in Indonesia